2018
DOI: 10.1007/s10554-018-1311-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of superficial coronary vessel wall deformation and stress: validation of in silico models and human coronary arteries in vivo

Abstract: Cyclic biomechanical stress at the lumen-intima interface plays a crucial role in the rupture of coronary plaque. We performed a comprehensive assessment of a novel angiography-based method for four-dimensional (4D) dynamic assessment of superficial wall stress (SWS) and deformation with a total of 32 analyses in virtual stenosis models with equal lumen dimensions and 16 analyses in human coronary arteries in vivo. The in silico model analyses demonstrated that the SWS, derived by the proposed global displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In silico and in vivo studies have revealed that angiographybased assessment of dynamic coronary artery deformation allows computation of superficial wall strain and stress, as reported by Wu et al (10,11,14). Lipid-rich plaque models had numerically higher wall stress than calcified and fibrous plaques, and wall stress increased with plaque burden.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In silico and in vivo studies have revealed that angiographybased assessment of dynamic coronary artery deformation allows computation of superficial wall strain and stress, as reported by Wu et al (10,11,14). Lipid-rich plaque models had numerically higher wall stress than calcified and fibrous plaques, and wall stress increased with plaque burden.…”
Section: Discussionmentioning
confidence: 80%
“…Coronary angiograms with minimal vessel image overlap and foreshortening are selected (13). Several key time-points during the cardiac cycle are identified from the electrocardiogram or according to the different stages of vessel motion during heart contraction and relaxation (Figure 2) (14). The number of frames for cardiac cycle can be determined from one QRS wave to the next on the electrocardiogram, when available.…”
Section: Calculation Mehtods Of Angiography-based 4d Coronary Artery Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed calculations to determine the volume flow rate of native coronary arteries that were not measured during surgery based on the previous research of Gould et al 21 With appropriate setting of boundary conditions, WSS values were calculated following an equivalent form, τ ¼ 4 μQ/πR 3 , where τ and μ are WSS value and dynamic blood viscosity, respectively, and R and Q represent the inner vessel radius and volume flow rate, respectively. For postprocessing, the lumen of the LIMA was divided into 3mm length pieces and a bin-angle of 30 degrees, similar to Wu et al 22 The mean WSS values were calculated within every portion for statistical analyses.…”
Section: The Process Of Wss Analysismentioning
confidence: 99%
“…For postprocessing, the lumen of the LIMA was divided into 3-mm length pieces and a bin-angle of 30 degrees, similar to Wu et al 22 The mean WSS values were calculated within every portion for statistical analyses.…”
Section: Fundingmentioning
confidence: 99%